El currículum de matemáticas en la prueba de acceso - Goberna, M. A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper we present a comparison of the mathematic con:ents for the final -secondary school examination in England, France and Spain, giving, finally, a proposal in order to elaborate a new Spanish programme.